Pendampingan dan Sosialisasi Protokol Kesehatan Covid-19 sebagai Upaya Persiapan Pembelajaran Tatap Muka - Dhananjaya Y.H. Kumarajati; Amalia Cemara Nur’Aidha; Bopi Yudha Sapa (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
The Covid-19 pandemic has brought a significant impact on the world of education, including in Indonesia. In response, the Indonesian Ministry of Education and Culture issued Guidelines for the Implementation of Learning for the Second Semester of the 2020/2021 Academic Year during the Covid-19 Pandemic on November 20, 2020. SMK Kesehatan Binatama, an accredited "A" educational institution in Sinduadi Village focusing on health sciences, has also felt the impact of this pandemic. A SWOT analysis conducted at SMK Kesehatan Binatama revealed issues related to the school's readiness to meet the health protocol standards set by the government for face-to-face learning. As a solution, the school organized assistance and socialization of health protocols. The socialization and counseling aimed to increase knowledge and awareness about Covid-19, as well as efforts to prevent and reduce the risk of its transmission. The assistance focused on maintaining the consistency of health protocol implementation within the school environment. The steps for implementing community service begin with initial observation, identification of partner problems, application for community service permits, followed by implementation of training activities consisting of health protocol counseling and SOP preparation, and ending with mentoring activities consisting of mentoring risk mapping, compliance with risk implementation and preparation of SOPs. The result of this community service activity is to make Binatama Health Vocational School a role model and pilot project for implementing face-to-face learning in Sinduadi Village. This community service activity has targets and outcomes divided into two aspects: services and products. The service aspect includes improving the school's knowledge and readiness in dealing with Covid-19 and conducting face-to-face learning. The product aspect includes the creation of SOP documents and scientific articles